Targeting the Ras palmitoylation/depalmitoylation cycle in cancer. (16th June 2017) - Lin, David Tse Shen; Davis, Nicholas G.; Conibear, Elizabeth
Abstract : The Ras proteins are well-known drivers of many cancers and thus represent attractive targets for the development of anticancer therapeutics. Inhibitors that disrupt the association of the Ras proteins with membranes by blocking the addition of the farnesyl lipid moiety to the Ras C-terminus failed in clinical trials. Here, we explore the possibility of targeting a second lipid modification, S-acylation, commonly referred to as palmitoylation, as a strategy to disrupt the membrane interaction of specific Ras isoforms. We review the enzymes involved in adding and removing palmitate from Ras and discuss their potential roles in regulating Ras tumorigenesis. In addition, we examine other proteins that affect Ras protein localization and may serve as future drug targets.